2021
DOI: 10.1136/bmjopen-2020-047526
|View full text |Cite
|
Sign up to set email alerts
|

Development of influenza-associated disease burden pyramid in Shanghai, China, 2010–2017: a Bayesian modelling study

Abstract: ObjectivesNegative estimates can be produced when statistical modelling techniques are applied to estimate morbidity and mortality attributable to influenza. Based on the prior knowledge that influenza viruses are hazardous pathogens and have adverse health outcomes of respiratory and circulatory disease (R&C), we developed an improved model incorporating Bayes’ theorem to estimate the disease burden of influenza in Shanghai, China, from 2010 to 2017.DesignA modelling study using aggregated data from admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
1
8
1
Order By: Relevance
“… 5 The ageing population in Shanghai is on the rise, which is an important factor contributing to the persistently high influenza-associated mortality. 24 In 2019, about 4.7 million adults>60 years were registered in Shanghai, an increase of 48.51% compared with 2010, accounting for 32.05% of the total population. CVD had been the leading COD in older adults during this period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 5 The ageing population in Shanghai is on the rise, which is an important factor contributing to the persistently high influenza-associated mortality. 24 In 2019, about 4.7 million adults>60 years were registered in Shanghai, an increase of 48.51% compared with 2010, accounting for 32.05% of the total population. CVD had been the leading COD in older adults during this period.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Singapore found that the burden of influenza on CVD increased with age and was significantly associated with excess hospitalisations for CVD, mainly in people≥80 years old 5. The ageing population in Shanghai is on the rise, which is an important factor contributing to the persistently high influenza-associated mortality 24. In 2019, about 4.7 million adults>60 years were registered in Shanghai, an increase of 48.51% compared with 2010, accounting for 32.05% of the total population.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, some cases of hospitalization or mortality from the 2009/2010 season may have been missed in our study. However, studies from U.S., the United Kingdom, and China (Shanghai) indicate that since the decline of the 2009 H1N1 pandemic outbreak, the rates of hospitalization have increased again, with a peak during the 2017/2018 season [ 7 , 8 , 9 , 26 ]. These data are consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…The comparison was aimed to evaluate the accuracy of our estimates of influenza‐associated mortality. Furthermore, to externally validate our estimates, we compared the annual average influenza‐associated excess mortality among older adults aged 65 years and above after 2010 in two municipalities (Chongqing and Shanghai) 16,17,36 with that of corresponding cities from 2011 to 2016 in the main analysis and sensitivity analyses. Finally, we compared the provincial‐level variation trend of our estimated influenza‐associated excess R&C and AC mortality with that of influenza‐associated excess respiratory mortality published previously 3 .…”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge, Li et al estimated the national and provincial influenza‐associated excess respiratory mortality in older adults after the 2009 influenza pandemic in mainland China. 3 For influenza‐associated excess R&C or AC mortality, a few studies estimated mortality at the national or regional level before the 2009 influenza pandemic 4 , 10 or at the city level, such as Beijing, 15 Shanghai, 16 , 17 and Shenzhen. 18 To better understand the post‐pandemic influenza‐associated mortality burden among elderly individuals aged 65 years and above in mainland China, we used a systematic review and model method to estimate influenza‐associated excess R&C and AC mortality by province and nationwide from 2011 to 2016.…”
Section: Introductionmentioning
confidence: 99%